2016
DOI: 10.3109/08039488.2016.1162846
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of psychiatric indications for deep brain stimulation, with focus on major depressive and obsessive-compulsive disorder

Abstract: DBS may show promise for treatment-resistant OCD and MDD but the results are limited by small sample size and insufficient randomized controlled data. Deep brain stimulation for OCD has received United States Food and Drug Administration approval. Other psychiatric indications are currently of a purely experimental nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 63 publications
1
41
0
Order By: Relevance
“…Experimental neuromodulation via brain electrodes was first tried in patients with psychiatric disorders during the 1950s (Heath, Russell, Monroe, & Mickle, 1955). Since then, more than 120,000 neurological patients have been treated with DBS, whereas only an estimated 500 psychiatric patients received DBS (Benabid, 2003;Naesstr€ om, Blomstedt, & Bodlund, 2016). This might be explained in part by the historically rooted taboo on neurosurgical interventions for psychiatry, but also by the heterogenic symptomatology and complex neuroanatomy of psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental neuromodulation via brain electrodes was first tried in patients with psychiatric disorders during the 1950s (Heath, Russell, Monroe, & Mickle, 1955). Since then, more than 120,000 neurological patients have been treated with DBS, whereas only an estimated 500 psychiatric patients received DBS (Benabid, 2003;Naesstr€ om, Blomstedt, & Bodlund, 2016). This might be explained in part by the historically rooted taboo on neurosurgical interventions for psychiatry, but also by the heterogenic symptomatology and complex neuroanatomy of psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…However, these side effects are reversible and can be removed changing the stimulation parameters or turning off the neuropacemaker. The stimulation does not seem to result in any residual physiological changes when the treatment is discontinued [6].…”
Section: Deep Brain Stimulationmentioning
confidence: 99%
“…A burr hole is made on each side of the midline for the implantation of two electrodes (about 1.3 mm in diameter with several contacts at their distal end) and an extension cable is tunneled under the skin, connecting the electrodes with a neuropacemaker placed below the clavicle in a subcutaneous pocket. The hospitalization duration after surgery depends on time needed for programming the device, but usually patients are discharged within 3-5 days [6].…”
Section: Deep Brain Stimulationmentioning
confidence: 99%
“…1,3,20,27 Additionally, minimally invasive ablative procedures, such as stereotactic radiosurgery, retain a prominent role is affording patients relief from the symptoms of intractable OCD. A study of 5 patients who underwent bilateral anterior capsulotomy with Gamma Knife radiosurgery for refractory OCD revealed that 4 patients demonstrated marked clinical improvement, and the remaining patient demonstrated mild clinical improvement, as measured by reductions in Yale-Brown Obsessive-Compulsive Scale scores.…”
Section: Ethical Considerations and The Future Of Psychosurgerymentioning
confidence: 99%